KONSEP EKONOMI AL-GHAZALI - Lilih Rahmawati (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2015)
This paper of the discussion focuses on the concept of economic thought of al-Ghazali. The main reason for choosing al-Ghazali's economic concept is since it coins its own peculiarities compared to that of other thinkers. In his grand concept of economy, al-Ghazali focused on the behavior of individual within the perspective of al-Qur'an, al-Sunnah, fatwa of prophet Muhammadâ€™s companions, and the attendants of his companions as well as the leading sufis such asÂ Junayd al-Baghdady, Zun al-Mishri, and Harith bin Asad al-Muhasibi. This paper also discusses about how is exactly the economic concept of al-Ghazali? Writer of this paper concludes that al-Ghazaliâ€™s thought in the economic field is inclined to moral ethics. Al-Ghazali based his economic concept on that of sufis since at the time the riches and the official governments were full of prestige to accept the fiqh (Islamic jurisprudence) and philosophical approach. Muslim economists have more contributions to economic development not only in Islamic environment, but also conventional economy. The author of this paper, with the discussion of the economic thought of the Muslim thinkers, hopes that the discourse of Islamic economy in academic circles becomes more lively. Furthermore, the nuances of Islamic economy in Indonesia can grow and operate the Islamic financial institutions in Indonesia increasingly and comprehensively.